Positron emission tomography/computed tomography perfusion imaging with myocardial blood flow has diagnostic and prognostic value for cardiac allograft vasculopathy. (3rd October 2022) - Abadie, B; Chan, N; Sharalaya, Z; Bhat, P; Harb, S; Jacob, M; Tang, W H; Cremer, P; Jaber, W
Abstract: Background: Cardiac allograft vasculopathy (CAV) is a leading cause of morbidity and mortality in patients with orthotopic heart transplantation (OHT). Invasive coronary angiography is the traditional method of screening for and diagnosing CAV. Alternative non-invasive modalities have been sought to screen for CAV. A small, single-center study utilizing Positron Emission Tomography/Computed Tomography Perfusion Imaging (PET/CT) with stress myocardial blood flow (MBF) demonstrated good diagnostic and prognostic value for CAV. Purpose: The purpose of this study was to validate the proposed algorithm for diagnosing and prognosticating CAV by PET/CT with stress MBF in a large and contemporary series. Methods: Patients with a history of OHT with no prior revascularization in the transplanted heart who underwent PET/CT with MBF were included in the prognostic portion of the study. For the diagnostic value of PET/CT with MBF, only patients who had a PET/CT within 12 months of coronary angiography were included. The diagnostic accuracy of PET/CT was compared to the most recent coronary angiogram. A composite outcome of death, heart failure hospitalization, acute coronary syndrome, revascularization, and re-transplantation was used to validate the prognostic ability of PET/CT with MBF. Results: 450 PET/CT scans with MBF were performed and included in the prognostic portion of the study. 78 patients had PET/CT within 12 months of coronary angiography and were included in the diagnostic portion. Normal perfusion with normal myocardial blood flow had a 100% negative predictive value for moderate-severe CAV by angiography. PET/CT CAV 2/3 had a positive predictive value of 69% for moderate-severe CAV. Over 24 months, there were 20 events in the 39 patients with a PET CAV grade of 2/3 versus 21 events in the 411 patients with a PET CAV grade of 0/1 with a hazard ratio 13.3 (p<0.001). Conclusions: The current proposed algorithm for diagnosing CAV by PET/CT with stress MBF has excellent negative predictive value along with good positive predictive value for detecting moderate-severe CAV by coronary angiography. A PET/CT with stress MBF with CAV classification of 2/3 is associated with a poor prognosis. Funding Acknowledgement: Type of funding sources: None.